Post-Traumatic Stress Disorder, Mobile Phone Dependence, and Academic Boredom in Adolescents During the COVID-19 Pandemic - Shen, Lingyan; Wu, Xinyue; Zhen, Rui; Zhou, Xiao (Frontiers in Psychology, 2021)
Background. The COVID-19 epidemic has affected adolescents’ mental health and even elicited their academic problems. Post-traumatic stress disorder (PTSD) and academic boredom are common negative psychological reactions to the epidemic. PTSD might be related to academic boredom, but the underlying mechanism of this potential relation in the context of the COVID-19 epidemic remains unclear. We investigated this with consideration to the job demands–resources model and the model of compensatory internet use. Aims. To examine the mediating role of mobile phone dependency in the relation between PTSD and academic boredom. Methods. Six hundred and eighty-three middle school students in Hubei Province were investigated using self-report questionnaires. SPSS19.0 was used for the descriptive analysis and correlation analysis, and Mplus7.0 was used for structural equation modeling to test the mediating role of mobile phone dependence in the relation between PTSD and academic boredom. Results. PTSD symptoms were associated positively with academic boredom, and mobile phone dependence played a mediating role in the relation between PTSD and academic boredom. Specifically, adolescents with severe PTSD symptoms tended to report greater dependency on mobile phones, and hence show higher levels of boredom in learning. Conclusion. PTSD symptoms of adolescents directly aggravated their academic boredom, and indirectly affected academic boredom by increasing their dependence on mobile phones.